La manzana de piedra de Albalucía Ángel: entre “Barbazul” y el desmantelamiento de paradigmas patriarcales - Garavito, Lucía (Latin American Theatre Review, 2010)
La manzana de piedra, an unpublished play by Angel, fits into the category of texts that explore “writing beyond the ending” (Rachel Blau DuPlessis). It unmasks and deconstructs cultural forms responsible for women’s oppression while reformulating a new feminine subject, free of the constraints imposed by family, community and tradition. “Barbazul” and the forbidden chamber motif provide the subtext for the exploration of domestic violence as experienced by women generation after generation. Virginia Woolf’s room of one’s own, on the other hand, represents for Angel the possibility of a transgressive, creative and critical space where women can propose their own way of being and doing in today’s world. (LG, Article in Spanish)